Pengaruh Luas Penutupan Terumbu Karang Pada Lokasi Biorock dan Reef Seen Terhadap Keragaman Spesies Ikan di Wilayah Perairan Pemuteran, Bali [Closure Area Effect On Reefs Rehabilitation in Biorock and Reef Seen Habitat Against Fish Species Diversity In Regional Aquatic Pemuteran, Bali ] - A. Shofy Mubarak; Destya Twinandia; Akhmad Taufiq Mukti (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract This study aims to determine the percentage of coral reefs with extensive closure Biorock method and determine the relationship between the percentage of closure on the abundance of fish species in the area of rehabilitation with Biorock method. The study was conducted at two locations, locations with Biorock and natural reefs (Reef Seen). Research carried out by using the line transect method or Point Intercept Transect (PIT) with a direct enumeration technique Cencus Visual Method (VCM) and photo transects for data reef fish and coral reef data. Transects installed in locations that have been selected, the depth of 8 m. The main parameters studied, namely the abundance of coral and fish species identified at the sites. Supporting the studied parameters of physical and chemical parameters of waters, including: temperature, salinity, water pH and brightness and the percentage cover of coral. Measurement of water quality, including: temperature, depth, salinity, acidity and brightness. The results of this research is vast percentage of coral cover on the location Biorock of 38.5% with the type of branching Acropora growth, while at the location of Reef Seen by 43.5% to the type of hard coral growth form of corals that dominate submasif. The percentage of coral cover has no influence on the abundance of species of reef fish in the territorial waters of Pemuteran, Bali.